Resolving disputes in telecommunications : global practices and challenges - Prasad, R. U. S (New Delhi : Oxford University Press, 2011)
This book provides in-depth account of telecommunications policy, regulation, and dispute resolution in India. It analyses current country practices and their unique features, and studies methods of dispute resolution in other countries as well.
CONTENTS: Foreword -- Acknowledgements -- List of abbreviation -- Overview -- Appendix i -- The national telecom policy of india, 1994 -- appendix ii -- India's new telecom policy, 1999 -- Appendix iii: case study on the need for conducive environment; appendix -- Case study on scope of service and jurisdictional issues -- Appendix -- tdsat India decision on license fees -- Appendix -- tdsat India procedures -- References.
Includes bibliographical references (p. [188]-193) and index
Keywords: Dispute resolution (Law); Dispute resolution (Law) -- India; Telecommunication -- Law and legislation; Telecommunication -- Law and legislation -- India